2006
DOI: 10.1007/s10832-006-2402-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of additives on Cu electrodeposits: electrochemical study coupled with EQCM measurements

Abstract: The effect of polyethylene glycol (PEG) and chloride ions on Cu electrodeposition mechanism is investigated. Using blank electrolyte, electrochemical measurements show that PEG adsorbs more or less on the electrode surface depending on the nature of this surface (copper, gold). Alternative current techniques and electrochemical quartz crystal microbalance (EQCM) experiments are performed at open circuit and under polarisation. They show that the PEG adsorption on the Cu electrode is weak at open circuit, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…40 However, the cathodic current increased up to Ϫ1.7 V because of the hydrogen evolution reaction at higher cathodic peak potential. 50,51 This observation was supported by earlier reports, 50,51 and they found that a continuous mass increase is observed as the potential is scanned in the cathodic direction during the deposition of Cu-NPs. After the frequency change during the potential scanning from Ϫ0.4 to Ϫ1.7 V, the amount of Cu NPs deposited on the PoPD film was estimated to be +422 ng.…”
Section: Resultssupporting
confidence: 82%
“…40 However, the cathodic current increased up to Ϫ1.7 V because of the hydrogen evolution reaction at higher cathodic peak potential. 50,51 This observation was supported by earlier reports, 50,51 and they found that a continuous mass increase is observed as the potential is scanned in the cathodic direction during the deposition of Cu-NPs. After the frequency change during the potential scanning from Ϫ0.4 to Ϫ1.7 V, the amount of Cu NPs deposited on the PoPD film was estimated to be +422 ng.…”
Section: Resultssupporting
confidence: 82%
“…The parameters from both the area roughness and grain size analysis show that the roughness of Cu films from electrolyte solutions containing MG is greater than 5 times smaller than that of Cu films from additive-free solutions. Similar leveling and brightening effects of additives on Cu electrodeposits have been observed for polyethylene glycol (PEG) + Cl − , and 4,5-dithiaoctane-1,8-disulfonic acid (SPS) + PEG systems, 33,34 but the smoothing effect of MG in this work appears to be more significant than that for PEG + Cl − . 34 3.3.3.…”
Section: Afm Study Of Film Morphologiessupporting
confidence: 80%
“…These experiments involved scans proceeding from the OCP in the cathodic direction to −0.9 V. All solutions had a base composition of 0. 25 As the solution was added, the working electrode rotation speed was increased to 2000 rpm for a few seconds to homogenize the contents and then reduced back to 500 rpm. The current was monitored during the pause and the scan not resumed until a total time of 10 min had elapsed.…”
Section: Methodsmentioning
confidence: 99%
“…13,19,22,23 Experimental evidence from several techniques has indicated that little or no PEG adsorbs on copper in the absence of Cl − . 19,[24][25][26][27] The ability of Cl − and PEG to inhibit Cu 2+ reduction is affected by their concentrations, PEG molecular weight, and electrode potential. 8,11,[13][14][15]19,22,23,25,[28][29][30][31][32][33] Inhibition increases with Cl − concentration up to a limit at fixed PEG concentration.…”
mentioning
confidence: 99%